Directions of high speed organization motor transport report Kyiv–Dnepro - Pasichnyk, A. M.; Lebid, I. H.; Miroshnichenko, S. V. (Systems and Technologies, 2019)
The article shows that the availability of modern transport infrastructure is a prerequisite for sustainable economic development of the state. Consequently, the development of transport infrastructure is planned taking into account strate-gic goals and is based on the realization of a sufficient level of mobility of trans-portation using modern highways. The substantiation of the relevance of the im-provement and development of the methodology for the development of various elements of the transport infrastructure, rolling stock and technologies for the organization of high-speed traffic was made.As a result of the study it was found that almost half of the population’s needs in passenger and freight transportation are provided by road transport. According to expert estimates the problem of restoring and modernizing the Ukrainian road net-work to ensure high-speed transportation is of strategic importance, since their con-dition is generally unsatisfactory. Thus, according to the results of the analysis, it was established that the Ukrainian public highways have more than 3 million square meters. m yam, about 56 thousand km of roads that require updating of road mark-ings, more than 20 thousand km of roads, where it is necessary to remove natural landfills and on most roads it is necessary to cut down overgrowths. In addition, a separate more than 50 % of the roads do not meet the requirements for equality, and about 40% – for strength. Accordingly, the average speed on Ukrainian roads is 2–3 times lower than in Western European countries.The results of the analysis of the condition of highways suitable for organiz-ing high-speed traffic on the Kyiv–Dnipro route are presented and the main di-rections for its implementation are identified. The calculations of the permissible technical parameters of the movement of vehicles on certain routes. It is shown that the proportion of heavy and large-sized vehicles grows in the transport flows, which leads to the rapid destruction of roads and bridges, which are designed for much smaller volumes and loads. For the introduction of high-speed traffic pro-posed measures to improve the technical level of existing roads. The necessity of intensifying the modernization and repair of roads in Ukraine based on the use of modern technologies, which will create the necessary conditions for the introduc-tion of high-speed road transport.